CARD-Associated Risk Score Features the Immune Landscape and Predicts the Responsiveness to Anti-PD-1 Therapy in IDH Wild-Type Gliomas - Li, Depei; Hu, Wanming; Lin, Xiaoping; Zhang, Ji; He, Zhenqiang; Zhong, Sheng; Wen, Xia; Zhang, Peiyu; Jiang, Xiaobing; Duan, Hao; Guo, Chengcheng; Wang, Jian; et al. (Frontiers in Cell and Developmental Biology, 2021)
Background: Proteins containing the caspase recruitment domain (CARD) play critical roles in cell apoptosis and immunity. However, the impact of CARD genes in tumor immune cell infiltration, responsiveness to checkpoint immunotherapy and clinical outcomes of gliomas remains unclear. Here, we explore using CARD genes to depict the immune microenvironment and predict the responsiveness of gliomas to anti-PD-1 therapy. Methods: The genome and transcriptome data of 231 patients with isocitrate dehydrogenase wild-type (IDH-wt) gliomas were retrieved from The Cancer Genome Atlas (TCGA) database to screen CARD genes associated with T lymphocyte infiltration in gliomas. Weighted co-expression network and LASSO penalized regression were employed to generate a CARD-associated risk score (CARS). Two independent and publicly available datasets were used to validate the effectiveness of CARS. Results: The CARS divided the 231 glioma patients into high- and low-risk subgroups with distinct immune microenvironment and molecular features. The high-risk group had high CARS and was characterized by enrichment of dysfunctional T-lymphocytes in a profound immunosuppressive microenvironment, whereas the low-risk group had low CARS and exhibited an immune exclusion genotype. Moreover, signaling aberrations including upregulation of PI3K/Akt/mTOR, NF-κB and TGF-β were found in high-risk group. In contrast, activated WNT pathway was more evident in low-risk group. Furthermore, we found that an elevated CARS indicated a decreased overall survival for IDH-wt gliomas under standard care but a clinical benefit from checkpoint immunotherapy. Conclusions: This study developed an immune- and prognosis-relevant risk score, which could be used to enhance our understanding of the heterogeneity of immune microenvironment of gliomas and facilitate to identify patients who will benefit from checkpoint immunotherapy.